1994
DOI: 10.2307/3431960
|View full text |Cite
|
Sign up to set email alerts
|

The Biochemical Effects of Physiologic Amounts of Dietary Boron in Animal Nutrition Models

Abstract: 35-43 (1994)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 20 publications
(21 reference statements)
0
38
0
1
Order By: Relevance
“…As an essential nutrient, B is a necessary dietary for not just to metabolisms of bacteria, fungi, plants, animals and but also to humans (Hunt, 1994;Goldbach et al, 2001). B, like other microelements, could be toxic in definite doses, depending on how organisms taken in (Blevins and Lukaszewski, 1994).…”
Section: Resultsmentioning
confidence: 99%
“…As an essential nutrient, B is a necessary dietary for not just to metabolisms of bacteria, fungi, plants, animals and but also to humans (Hunt, 1994;Goldbach et al, 2001). B, like other microelements, could be toxic in definite doses, depending on how organisms taken in (Blevins and Lukaszewski, 1994).…”
Section: Resultsmentioning
confidence: 99%
“…However, boron at the doses of 200 and 400 mg/L decreased their body weights [24] . Hunt [7] reported that different doses of boron with vit D caused an increase in the body weight of the chicks. King et al [13] , reported that different doses of boron injected into the egg had no effect on the body weight.…”
Section: Discussionmentioning
confidence: 99%
“…It is beneficial for bone structure and functions and plays role in inflammation process as well as in regulation of the physiologic functions [1,7,8] . It was shown that boron did not exhibit toxic effects on the reproduction system of rats and was found to be effective on skeletal system at high doses [9] .…”
Section: Introductionmentioning
confidence: 99%
“…Hunt (1989) demonstrated that boron deficiency lead to poor growth and leg abnormalities in chicks. Recent research findings suggested that physiological amounts of supplemental dietary boron affected a wide range of metabolic parameters in the chick and rat (Hunt 1994). Another study showed that microscopic changes were seen in kidney and nervous system of mice, rats and dogs following exposure to BA (Pfeiffer et al 1945).…”
Section: Introductionmentioning
confidence: 99%